A critical analysis of the United Nations Organisation mission in the Democratic Republic of Congo : a focus on MONUC - Zvobgo, Tafadzwa (Department of Political Studies, 2016)
Critical discussions on United Nations (UN) peacekeeping operations are primarily failurefocused and seek to reform those operations, thus limiting the literature about peacekeeping and its results. This dissertation intends to expand the scope of inquiry into UN peacekeeping operations by critically analysing the United Nations Organisation Mission in the Democratic Republic of Congo (MONUC). It accomplishes this by examining how MONUCs United Nation Security Council mandates and objectives (its prioritisation and interpretation of mission mandates) impacted the mission. In addition, it includes an examination of MONUCs accomplishments.